Manajemen Public Relations Asia Pacific Rayon dalam Mengkomunikasikan Sustainable Fashion - Dona Bella; Riki Arswendi (COMMUNICATION MAJOR, 2023)
Sustainable fashion is a fashion product that aims to invite the people of Indonesia to maintain environmental conservation. Where Asia Pacific Rayon as a company that produces environmentally friendly products has an important role in communicating it to the general public. How Asia Pacific Rayon's Public Relations management communicates Sustainable Fashion products is the purpose of this research. This research uses qualitative methods with a descriptive approach. The results showed that Asia Pacific Rayon in communicating sustainable fashion in accordance with the concept of public relations management, namely; Fact Finding, finding the focus of the problem. Planning, preparing a communication program plan. Communication, providing collaborative space at Jakarta Fashion Hub (JFH), creating content in offline and online media, especially social media. Evaluating, conducting periodic evaluations of various organizational activities both self-managed and colaboration events.Keywords: Asia Pacifc rayon; Public Relations Management; sustainable fashion.